Assessment of biofilm formation by Scedosporium apiospermum, S. aurantiacum, S. minutisporum and Lomentospora prolificans. Issue 7 (8th August 2016) - Mello, Thaís P.; Aor, Ana Carolina; Gonçalves, Diego S.; Seabra, Sergio H.; Branquinha, Marta H.; Santos, André L. S.
Abstract: Reported herein is the ability of Scedosporium apiospermum, S. aurantiacum, S. minutisporum and Lomentospora prolificans conidia to adhere, differentiate into hyphae and form biofilms on both polystyrene and lung epithelial cells. To different degrees, all of the fungi adhered to polystyrene after 4 h, with a predominance of those with germinated conidia. Prolonged fungi–polystyrene contact resulted in the formation of a monolayer of intertwined mycelia, which was identified as a typical biofilm structure due to the presence of a viable mycelial biomass, extracellular matrix and enhanced antifungal resistance. Ultrastructural details were revealed by SEM and CLSM, showing the dense compaction of the mycelial biomass and the presence of channels within the organized biofilm. A similar biofilm structure was observed following the co-culture of each fungus with A549 cells, revealing a mycelial trap covering all of the lung epithelial monolayer. Collectively, these results highlight the potential for biofilm formation by these clinically relevant fungal pathogens.